A study on biological rhythms of Himalayan Pashmina goats. Issue 7 (2nd October 2020) - Iqbal Yatoo, Mohd.; Bhat, Riyaz Ahmad; Muheet,; Parray, Oveas Raffiq; Shabir, Mir; Kubrevi, Syed Shafat; Dar, Rukhsar Ahmad; Angmo, Kunzes; Kanwar, Maheshwar Singh
ABSTRACT: Biological rhythms may play an important role in the physio-reproductive lifecycle of Pashmina goats. However, such a study is lacking. Present study focuses on same. A total of 30 female Pashmina goats ( N  = 30) from 3 flocks ( n  = 10) having 10 animals each were selected randomly in 3 villages of Changthang, Ladakh (India). Average life span was 9.93 ± 0.462 years, body weight of adult female was 23.0 ± 1.08 kg and age of puberty was 11.93 ± 0.55 months. Average duration of oestrus cycle was 20.73 ± 0.23 days and that of standing estrus was 36.40 ± 1.67 h. Seasonal breeding was noted with breeding cycle being influenced by light hours. Average gestation length was 149.5 ± 1.05 days, frequently single kidding and usually singlets were born. Pashmina wool grows during winter season and starts shedding from spring. Seasonal cyclicity of diseases including neonatal diarrhea, endo-ectoparasitic infections, and respiratory infections [contagious caprine pleuropneumonia (CCPP)/peste des petits ruminants (PPR)] was noted. No significant difference ( p  > 0.05) of biological rhythms was noted in the three villages. This study provides the baseline data for biological rhythms of Pashmina goats that can have both physio-biological- and production- related importance.